(untitled) (Research, Society and Development, 2020)
This study is aimed to find out the language attitude of Simalungun people toward vernacular maintenance in Pematang Siantar. The data were collected from the Simalungun people living in Sitalasari district Pematang Siantar regency. The study employs qualitative research design with some informant’s consent with the need of this research to get understanding. The subjects of this study were 18 Simalungun people (17 years old to 25 years old). The instruments used for collecting data were questionnaire sheet, observation sheet, recording and interview. The data from questionnaire sheet were used to examine the language attitude. The findings show that there are 10 (55, 6 %) informants who have negative attitude and 8 (44. 4 %) informants have the positive attitude. These are influenced by three different factors which affect the attitude, namely; the tendency of language disloyalty, lack of pride and unawareness of the norm. This causes the language to be less frequency in use particularly in daily social life communication.